Management of Mandibular Angle Fracture in a 9-year-old with Miniplate and Monocortical Screws: A Clinical Challenge - Shunmugavelu, Karthik (Int J Clin Pediatr Dent, 2017)
The main characteristic feature of the pediatric mandible is that of decreased dimension, which leads to compromises in the open reduction and internal fixation (ORIF). In the dental segment, the cervically bulbous short stature primary teeth might act an obstacle during the maxillomandibular fixation conventionally. An increased osteogenic potential of bones favors rapid consolidation and remodeling in the affected region. The mixed dentition of the ugly duckling stage adds more burden while stabilizing the fractured segments. The main goal of the clinician is to achieve and restore the facial appearance and function. Hereby, we present a clinical challenge depicting a 9-year-old male with mandibular angle fracture managed by miniplate and monocortical screws fixation. How to cite this article: Shunmugavelu K, Subramaniam K. Management of Mandibular Angle Fracture in a 9-year-old with Miniplate and Monocortical Screws: A Clinical Challenge. Int J Clin Pediatr Dent 2017;10(4):391-393.